Mergers & Acquisitions in Indian Forging Industry - Chauhan, Vineet (2007)
This research aims at the detailed analysis of Indian Forging Industry with relation to the Mergers and Acquisitions undertaken globally. From past several years, Indian Automotive Industry is witnessing positive movements in the business. The dissertation mainly focuses on the impact of Mergers and Acquisitions on the performance of the acquiring company. Bharat Forge Ltd. (India) has been taken as the case study for the dissertation. The first section of the dissertation includes the nature of the Indian Forging Industry. The performance of the same has been analyzed and the future prospects have been discussed in detail. The second section of the dissertation following the above, gives details about the theoretical literature on the concept of Mergers and Acquisitions. It provides with the details such as Types, Synergies, Motives, Drivers, Funding and Approaches to measure Mergers and Acquisitions. The motto of the dissertation is to relate the impact of Mergers and Acquisitions on the profitability of the company. Hence, this section also throws light on the academic aspect of the profitability analysis of Mergers and Acquisitions. In the third section, we discuss about the company itself, Bharat Forge Ltd. (India). With a detailed introduction about the company in the beginning, we will then discuss about its global presence and product portfolio. In the later part of this section, we would pay stress to the acquisitions undertaken by Bharat Forge Ltd. In the fourth section, a detailed analysis of the various financial aspects of the company in its post acquisition period is carried out. This section also covers the financial interpretation through the use of the key financial ratios and the percentage changes in the financial outcomes yearly. These results have been represented graphically. The last section of the dissertation underlines the interpretation and the analysis of the research conducted followed by the various limitations of the study.